Alkynylated phenazines: synthesis, characterization, and metal-binding properties of their bis-triazolyl cycloadducts - Bryant, Jonathan; Lindner, Benjamin; Bunz, Uwe H. F. (The journal of organic chemistry, 2012)
We have synthesized a series of ethynylated phenazines and their bis-triazolyl cycloadducts to serve as metal ion sensors. Binding of metal ions is achieved through coordination to the phenazine nitrogen atom and the triazole ring. To allow metal sensing in aqueous solution, the triazole units are substituted with water-soluble ethylene glycol chains. These phenazine cycloadducts exhibit a selective affinity for binding silver ions. Examination of the halogenated analogues reveals a lowering of the band gap and the corresponding bathochromic shifts in the absorption and emission spectra. The electron-withdrawing properties of these halogens also result in significantly decreased metal-binding activity of the phenazine cycloadducts.